Joint associations of metabolically healthy abdominal obesity and non-alcoholic fatty liver disease with prediabetes and diabetes in Chinese adults. Issue 1 (25th August 2021) - Zhang, Junfeng; Xu, Qiaoyan; Lai, Fangfang; Chen, Ning; Lin, Mingzhu; Liu, Yongwen; Zhang, Wei; Liu, Changqin; Wang, Shunqin; Li, Zhibin
Abstract : Introduction: We aimed to evaluate the joint associations of metabolically healthy abdominal obesity (MHAO) with non-alcoholic fatty liver disease (NAFLD) on risks of diabetes and prediabetes. Research design and methods: Baseline information of 1318 adults with abdominal obesity (waist circumference ≥90 cm for men and 80 cm for women) from an ongoing cohort study in Xiamen, China were analyzed. Metabolic health was identified as none of the criteria of metabolism syndrome, except for obesity, was met. Results: MHAO and metabolically unhealthy abdominal obesity (MUAO) were identified on 173 (13.1%) and 1145 (86.9%) subjects. NAFLD was further diagnosed on 60 (34.7%) in MHAO and 721 (63.0%) in MUAO groups (p<0.001). Both MUAO (vs MHAO) and NAFLD (vs non-NAFLD) were independently associated with increased risks of diabetes as well as prediabetes plus diabetes, with the adjusted ORs (95% CIs) of 9.40 (3.38 to 26.14) and 2.02 (1.47 to 2.77), respectively. Compared with MHAO and non-NAFLD, MHAO and NAFLD showed significantly increased risks of prediabetes plus diabetes with the adjusted ORs (95% CIs) of 2.87 (1.32 to 6.27, p=0.008). And there were significantly positive trends between increasing categories jointly by MHAO and NAFLD (from MHAO and non-NAFLD, MHAO and NAFLD, MUAO and non-NAFLD to MUAO and NAFLD) with risks of diabetes and prediabetes plus diabetes (both trend tests: p<0.001). Conclusions: About 35% of subjects with MHAO accompanied by NAFLD showed excessive risk of prediabetes plus diabetes compared with MHAO and non-NAFLD. Thus, NAFLD should be screened and intervened even for those subjects with metabolically healthy obesity (MHO) and should be considered as one additional criterion when defining and diagnosing MHO.